Modeling self-sustaining waves of exothermic dissolution in nanometric Ni-Al multilayers. (November 2016) - Turlo, V.; Politano, O.; Baras, F.
Abstract: The self-sustained propagating reaction occurring in nanometric metallic multilayers was studied by means of molecular dynamics (MD) and numerical modeling. We focused on the phenomenon of the exothermic dissolution of one metallic reactant into the less refractory one, such as Ni into liquid Al. The exothermic character is directly related to a negative enthalpy of mixing. An analytical model based on the diffusion-limited dissolution [1] coupled with heat transfer was derived to account for the main aspects of the process. Together, several microscopic simulations were carried out. The first series were set up to obtain all the parameters governing the process, including the heat release by dissolution. The second series of MD simulations was set up to detect the very possibility of self-sustaining propagation driven by exothermic dissolution. We aimed at developing a consistent multiscale description by numerically solving the model with the MD extracted parameters. The study proves that the exothermic intermixing of Ni and Al is a driving mechanism of self-sustaining propagation in reactive nanofoils. Graphical abstract: